Berberine Ameliorates Prenatal Dihydrotestosterone Exposure-Induced Autism-Like Behavior by Suppression of Androgen Receptor - Xiang, Dongfang; Lu, Jianping; Wei, Chongxia; Cai, Xiaofan; Wang, Yongxia; Liang, Yujie; Xu, Mingtao; Wang, Zichen; Liu, Min; Wang, Min; Liang, Xuefang; Li, Ling; et al. (Frontiers in Cellular Neuroscience, 2020)
Many epidemiology studies have shown that maternal polycystic ovary syndrome (PCOS) results in a greater risk of autism spectrum disorders (ASD) development, although the detailed mechanism remains unclear. In this study, we aimed to investigate the potential mechanism and provide a possible treatment for PCOS-mediated ASD through three experiments: Experiment 1: Real time PCR and western blots were employed to measure gene expression in human neurons, and the luciferase reporter assay and chromatin immunoprecipitation (ChIP) were used to map the responsive elements on related gene promoters. Experiment 2: Pregnant dams were prenatally exposed to dihydrotestosterone (DHT), androgen receptor (AR) knockdown (shAR) in the amygdala, or berberine (BBR), and the subsequent male offspring were used for autism-like behavior (ALB) assay followed by biomedical analysis, including gene expression, oxidative stress and mitochondrial function. Experiment 3: The male offspring from prenatal DHT exposed dams were postnatally treated by either shAR or BBR, and the offspring were used for ALB assay followed by biomedical analysis. Our findings showed that DHT treatment suppresses the expression of estrogen receptor β (ERβ) and superoxide dismutase 2 (SOD2) through AR-mediated hypermethylation on the ERβ promoter, and BBR treatment suppresses AR expression through hypermethylation on the AR promoter. Prenatal DHT treatment induces ERβ suppression, oxidative stress and mitochondria dysfunction in the amygdala with subsequent ALB behavior in male offspring, and AR knockdown partly diminishes this effect. Furthermore, both prenatal and postnatal treatment of BBR partly restores prenatal DHT exposure-mediated ALB. In conclusion, DHT suppresses ERβ expression through the AR signaling pathway by hypermethylation on the ERβ promoter, and BBR restores this effect through AR suppression. Prenatal DHT exposure induces ALB in offspring through AR-mediated ERβ suppression, and both prenatal and postnatal treatment of BBR ameliorates this effect. We conclude that BBR ameliorates prenatal DHT exposure-induced ALB through AR suppression, this study may help elucidate the potential mechanism and identify a potential treatment through using BBR for PCOS-mediated ASD.